Strategy Komunikasi Kementerian Pekerjaan Umum Dan Perumahan Rakyat Dalam Mensosialisasikan Peringatan Hari Air Sedunia 2018 - Qona'ah, Siti (Jurnal Komunikasi, 2018)
Abstract The Ministry of Public Works and Public Housing in 2018 World Water Day Convention carries out a communication strategy by socializing various activities in overcoming Clean Water problems. The 2018 world water day theme â€œNatural For Waterâ€, Activities carried out include Certification of Situ, Lake, Pond and Reservoir, Biopori Campaign and Rainwater Reservoir, Clean Action of Cikapundung River, Conservation of Nature for Water. This research is to find out the communication strategy of the Ministry of Public Works and Public Housing in Socializing the 2018 World Water Day Commemoration with the theme "Natural For Water". In this study researchers used a qualitative approach and case study, as a research method that illustrates that the communication strategy is to socialize world water day 2018 through increasing the supply of raw water accompanied by control and utilization will benefit the community in overcoming water problems in the long termÂ keywords: communication strategy, socialization